E-cigarette advertising exposure in e-cigarette naïve adolescents and subsequent e-cigarette use: A longitudinal cohort study. (June 2018) - Camenga, Deepa; Gutierrez, Kevin M.; Kong, Grace; Cavallo, Dana; Simon, Patricia; Krishnan-Sarin, Suchitra
Abstract: Objective: Electronic (E-) cigarettes are one of the most popular tobacco products used by adolescents today. This study examined whether exposure to advertisements in (1) social networking sites (Facebook, Twitter, YouTube, Pinterest/Google Plus), (2) traditional media (television/radio, magazines, billboards), or (3) retail stores (convenience stores, mall kiosks, tobacco shops) was associated with subsequent e-cigarette use in a longitudinal cohort of adolescents. Methods: Data were drawn from longitudinal surveys conducted in fall 2013 (wave 1) and spring 2014 (wave 2) of a school-based cohort attending 3 high schools and 2 middle schools in Connecticut. Adolescents were asked about tobacco use behaviors and where they had recently seen e-cigarette advertising at wave 1. We used logistic regression to determine whether advertising exposure at wave 1 increased the odds of e-cigarette use by wave 2, controlling for demographics and cigarette smoking status at wave 1. Results: Among those who have never used e-cigarettes in wave 1 (n = 1742), 9.6% reported e-cigarette use at wave 2. Multivariate logistic regression demonstrated that exposure to e-cigarette advertising on Facebook (OR 2.12 = p < 0.02) at wave 1, but not other venues, significantly increased the odds of subsequent e-cigarette use wave 2. Age, white race, and cigarette smoking at wave 1 also was associated with e-cigarette use at wave 2. Conclusion: This study provides one of the first longitudinal examinations demonstrating that exposure to e-cigarette advertising on social networking sites among youth who had never used e-cigarettes increases the likelihood of subsequent e-cigarette use. Highlights: E-cigarette advertising is present in multiple venues. We examined data from a longitudinal cohort of adolescents. Exposure to advertisements on Facebook was associated with subsequent e-cigarette use.